Emotion Goals in Music Performance Anxiety - Osborne, Margaret S.; Munzel, Brendan; Greenaway, Katharine H. (Frontiers in Psychology, 2020)
Performance anxiety can be debilitating, and so researchers and lay people alike tend to assume that it is desirable to downregulate this emotion. Yet, emerging perspectives in the emotion literature suggest that people sometimes aim to upregulate anxiety to aid performance. The present research investigated the emotion goals that musicians hold when performing. Drawing on a novel framework of emotion goals, the findings suggest that how people want to feel and how they want to appear to feel are determinants of performance anxiety. In Study 1 (N = 44), musicians mostly reported wanting to neither feel nor show anxiety during a performance, although a meaningful subset reported wanting to feel but not show anxiety during a performance. In Study 2 (N = 32), musicians who enacted an emotion goal to neither feel nor show anxiety reported less state unease and greater satisfaction with their performance than musicians who enacted a goal to feel but not show anxiety. This research yields insight into the emotion goals that musicians hold and how these goals influence desired performance outcomes.